IMPLEMENTASI METODE ROLE PLAYING DALAM MENGEMBANGKAN COMMUNICATION SKILLS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 PAGAR ALAM - Fitia Belfasari; Wulan Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background in this study is based on the lack of communication skills  of  students when participating in Islamic Religious Education learning. This study aims to determine the implementation of the role playing method  in developing  students' Communication Skills in Islamic Religious Education subjects at SMP Negeri 1 Pagar Alam. The research method uses a type of field research with a qualitative research approach. Data collection techniques use Observation, Interviews, and Documentation. Sample determination techniques use Purposive Sampling.  The results of this study show that the implementation of the role playing  method can develop communication skills in students, but not all students, but there are some students whose communication skills have developed. The implementation of  this role playing method  can provide the development of students' communication skills because it can provide direct opportunities to practice speaking, responsibility and the level of confidence of students in the learning process.